REVIEW OF ENERGY REGULATIONS ON SOLAR ENERGY (PV) IN SLOVENIA AND AUSTRIA - Franjo Pranjić (Journal of Energy Technology, 2024)
This paper describes the regulation of solar energy (PV) in Slovenia and Austria, what parties provides support and incentives and how, who is eligible and who is not. All the principal documents regulating this area in Slovenia and Austria are listed. The present value of support for PV installations and a comparison of support schemes are also presented.